BMPR1A antagonist differentially affects cartilage and bone formation during fracture healing. Issue 12 (6th April 2016) - Morgan, Elise F.; Pittman, Jason; DeGiacomo, Anthony; Cusher, Daniel; de Bakker, Chantal M. J.; Mroszczyk, Keri A.; Grinstaff, Mark W.; Gerstenfeld, Louis C.
ABSTRACT: A soluble form of BMP receptor type 1A (mBMPR1A‐mFC) acts as an antagonist to endogenous BMPR1A and has been shown to increase bone mass in mice. The goal of this study was to examine the effects of mBMPR1A‐mFC on secondary fracture healing. Treatment consisted of 10 mg/kg intraperitoneal injections of mBMPR1A‐mFC twice weekly in male C57BL/6 mice. Treatment beginning at 1, 14, and 21 days post‐fracture assessed receptor function during endochondral bone formation, at the onset of secondary bone formation, and during coupled remodeling, respectively. Control animals received saline injections. mBMPR1A‐mFC treatment initiated on day 1 delayed cartilage maturation in the callus and resulted in large regions of fibrous tissue. Treatment initiated on day 1 also increased the amount of mineralized tissue and up‐regulated many bone‐associated genes ( p = 0.002) but retarded periosteal bony bridging and impaired strength and toughness at day 35 ( p < 0.035). Delaying the onset of treatment to day 14 or 21 partially mitigated these effects and produced evidence of accelerated coupled remodeling. These results indicate that inhibition of the BMPR1A‐mediated signaling has negative effects on secondary fracture healing that are differentially manifested at different stages of healing and within different cell populations. These effects are most pronounced during the endochondral period and appear to be mediated by selective inhibition of BMPRIA signaling within the periosteum. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:2096–2105, 2016.